Cardiac Imaging Within Emergency CT Angiography for Acute Stroke Can Detect Atrial Clots - Popkirov, Stoyan; Schlegel, Uwe; Weber, Werner; Kleffner, Ilka; Altenbernd, Jens (Frontiers in Neurology, 2019)
Cardiac embolism is presumed to cause a significant portion of cryptogenic strokes. Transesophageal echocardiography may detect intracardiac thrombi, but this remains a rare finding, possibly because remnant clots dissolve spontaneously or following thrombolysis. Cardiac imaging within cerebral CT angiography might offer an alternative method for thrombus detection within hyperacute stroke assessment. In a proof-of-concept study we analyzed records of patients aged ≥60 years that presented with suspected stroke and underwent extended cerebral CT angiography as part of their emergency assessment. CT imaging of patients with ischemic stroke or transient ischemic attack (TIA) and atrial fibrillation and of those with embolic strokes of undetermined source (ESUS) was reviewed for intracardiac clots and other cardiac or aortic pathology. Over a period of 3 months 59 patients underwent extended CT angiography for suspected stroke, 44 of whom received a final diagnosis of ischemic stroke or TIA. Of those, 17 had atrial fibrillation, and four fulfilled ESUS criteria. Thrombi were detected within atrial structures on CT angiography in three cases. In two ESUS patients complex atheromatosis of the proximal ascending aorta with irregular and ulcerating plaques was detected. Cardiac imaging within emergency cerebral CT angiography is feasible and can provide valuable diagnostic information in a patient group that might not routinely undergo transesophageal echocardiography. A small change to emergency assessment could potentially uncover cardioembolic pathology in cases that would have remained cryptogenic otherwise.